Quaternary Research in Sri Lanka - Katupotha, K.N.J. (My University, 2014)
Attached

Quaternary is the era which saw the appearance of mankind. There is disagreement over the duration, with some scientists retaining a short time scale (600,000 years) while a majority accepting the long time – scale of 1.8 to 2.0 million years. It comprises two epochs – the Pleistocene and the Holocene. The Pleistocene epoch in Sri Lanka has been subdivided based on different types of fossils. These subdivisions are useful in the study of palaeomagnetic changers, geological formations and palaeolithic cultures in Sri Lanka. Radiometric dating of fossil coral and shells collected from the western and southern coastal zone suggested mid and late Holocene three high sea – level episodes between 6,240 and 2,270 yr B.P. However, there is a need for further investigations on the whole Quaternary period by different disciplines in order to reveal the nature of the palaeogeography, palaeoclimatology and palacoecology of Sri Lanka.